EFEKTIVITAS PENERAPAN MIND MAPPING PADA PEMBELAJARAN IPASS SISWA SEKOLAH DASAR KELAS TINGGI SE-KECAMATAN NGAWI - Ihsan Intania (Jurnal Riset Pendidikan Dasar Dan Karakter, 2024)
This study investigated the effectiveness of mind mapping in science learning at a high-grade primary school in Ngawi sub-district. The purpose of this study was to evaluate the extent to which the use of mind mapping can improve students' understanding of science concepts. The research methods used include construct validity test, Lawshe's CVR, reliability test with Cronbach's alpha formula, and hypothesis testing using Likert scale on questionnaire. Data were collected through questionnaires distributed to high school students in Ngawi District. The results showed that the use of mind mapping significantly improved students' understanding of science concepts, with a questionnaire reliability value of 0.8995 and 91% of respondents showing approval of this technique. The implication of this study is that mind mapping can be an effective tool in improving students' interaction with science learning materials, through visual representations that strengthen concept understanding.